2000
DOI: 10.1128/jvi.74.4.1641-1647.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cell Recognition by Foot-and-Mouth Disease Virus That Lacks the RGD Integrin-Binding Motif: Flexibility in Aphthovirus Receptor Usage

Abstract: Cell surface molecules that can act as virus receptors may exert an important selective pressure on RNA viral quasispecies. Large population passages of foot-and-mouth disease virus (FMDV) in cell culture select for mutant viruses that render dispensable a highly conserved Arg-Gly-Asp (RGD) motif responsible for integrin receptor recognition. Here, we provide evidence that viability of recombinant FMDVs including a Asp-1433Gly change at the RGD motif was conditioned by a number of capsid substitutions selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
179
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(184 citation statements)
references
References 63 publications
4
179
0
1
Order By: Relevance
“…Evaluation of receptor binding by using synthetic peptides. The nature of the binding of VpB1-KGE to cells was further evaluated by utilizing a peptide inhibition of plaque formation protocol similar to that reported by Baranowski et al (2). The results of these studies, shown in Fig.…”
Section: Genomicmentioning
confidence: 64%
See 2 more Smart Citations
“…Evaluation of receptor binding by using synthetic peptides. The nature of the binding of VpB1-KGE to cells was further evaluated by utilizing a peptide inhibition of plaque formation protocol similar to that reported by Baranowski et al (2). The results of these studies, shown in Fig.…”
Section: Genomicmentioning
confidence: 64%
“…Specifically, passage of virus in cell culture selects viruses with an expanded host range in cell culture and with altered amino acid residues on their capsid surfaces. In the case of the Chinese virus, the changes were clustered around the fivefold axis of the virion, in a region previously shown to be altered by very high level passage of a type C virus in cell culture (2,3,18,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that FMDV type O virus strains that contained a KGE sequence in place of the naturally occurring integrin-binding RGD are able to replicate well in cell culture (Zhao et al, 2003), whilst type C viruses have been reported to be capable of initiating infection in the absence of the highly conserved RGD motif (Martinez et al, 1997 andBaranowski et al, 2000). In this study, evidence was obtained indicating RNA replication and virus assembly of the genetically engineered vNAMKGE/SAT2 virus, despite its non-infectious phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue culture-adapted viruses can use heparan sulfate, a cell surface glycosaminoglycan, as a receptor to enter cells (Jackson et al, 1996 andSa-Carvalho et al, 1997). More recently, it has become apparent that FMDV may also use receptors of unknown identity that are neither integrin nor heparan sulfate (Martinez et al, 1997, Baranowski et al, 2000and Zhao et al, 2003, thus indicating the existence of other receptor molecules and alternative mechanisms for FMDV entry into cells.…”
Section: Introductionmentioning
confidence: 99%